USA Swimming Official Website
Offizielle Homepage des USA Schwimmverbandes. Unter dem Thema "Sportwissenschaft" sind folgende Informationen/Artikel zu finden: USA Swimming Sports Science General information and programs USA Swimming's sports science program "Success Through Science" program About the flume Nutrition for swimmers Training at altitude at the Olympic Training Center